2015
DOI: 10.1007/s00421-015-3179-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voluntary hypocapnic hyperventilation on the metabolic response during Wingate anaerobic test

Abstract: These results suggest that during short-period all-out exercise (e.g., 30-s WAnT), hypocapnia induced by voluntary hyperventilation reduces the aerobic metabolic rate without affecting exercise performance. This implies a compensatory elevation in the anaerobic metabolic rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…It is reasonable to assume that an OTC mouthguard has less contact between the teeth and gums compared to a custom-fit mouthguard; this may cause the total volume of the mouthguard to be greater and could lead to a reduction in the airway opening, thus inhibiting airflow. Although no mouthguards were used, this notion is corroborated by Fujii et al 13 . who found that higher minute ventilation (V E ) immediately following a WAnT led to lower [BL] values.…”
Section: Discussionmentioning
confidence: 74%
“…It is reasonable to assume that an OTC mouthguard has less contact between the teeth and gums compared to a custom-fit mouthguard; this may cause the total volume of the mouthguard to be greater and could lead to a reduction in the airway opening, thus inhibiting airflow. Although no mouthguards were used, this notion is corroborated by Fujii et al 13 . who found that higher minute ventilation (V E ) immediately following a WAnT led to lower [BL] values.…”
Section: Discussionmentioning
confidence: 74%
“…Despite such findings, the usefulness of VH as an ergogenic aid remains questionable with several studies finding no benefit to performance based outcomes 8,9,[16][17][18] . Hilbert et al 18 found no performance benefits to repeated bouts of handgrip exercise following VH in untrained males.…”
Section: Discussionmentioning
confidence: 99%
“…Jacob et al 3 determined that VH performed prior to a 50m swim resulted in significantly faster times. Additionally, Fujii et al 8 and Dobashi et al 9 found that 5 or 20min of VH prior to Wingate sprints resulted in similar peak and mean power outputs but lower O2 uptake. Sakamoto and colleagues 4 investigated the effect of 30 sec of VH during the rest periods between repeat cycling sprints.…”
Section: Introductionmentioning
confidence: 97%
“…(1,4) An interesting aspect is that the majority of investigations that have used the WAnT as physical performance index have analyzed the energy systems in isolation (6)(7)(8)(9)(10) or combined with the use of ergogenic aid. (11)(12)(13)(14)(15)(16)(17)(18) Undoubtedly, information produced by these studies has contributed a lot to understanding metabolic aspects and fatigue mechanisms related to high intensity exercise. Nevertheless, it is important to point out that in general in the above studies the analyses were performed by means of blood samples or muscular biopsy.…”
Section: Varied Emg Responses Of the Quadriceps Muscle During A Wingamentioning
confidence: 99%